2005
DOI: 10.1002/adsc.200404344
|View full text |Cite
|
Sign up to set email alerts
|

Control of Polymer Composition in Pd‐Catalyzed CO/Olefin Terpolymerization Reactions

Abstract: Abstract:The CO/tert-butylstyrene/ethylene terpolymerization catalyzed by Pd-(N-N') complexes was studied. The results evidence that the olefin preferentially inserted in the terpolymer chain is strictly related to the nature of the nitrogen ligand, mainly to its steric constraints, and not to the kind of ligand. Indeed, slight variations in the backbone of the nitrogen ligands coordinated to palladium allow for the synthesis of terpolymers with a controlled composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[51] This effect is shown in Figure 10 The cationic palladium systems [PdMe(NCMe)(N-NЈ)]-[BArF] containing imidazolyl-pyridine ligands cis-12, cis-13, cis-and trans-15 and pyrazolyl-pyridines 18, 20 and 21 have also been used for the terpolymerisation of CO/TBS/ ethene. [50,52] It was found that the choice of the olefin preferentially inserted into the terpolymer is strictly related to the nature of the nitrogen ligand present in the catalyst and not only to the kind of ligand. Thus, a slight modification in the chelating N ligands coordinated to palladium terpolymerisation catalysts leads to unexpected results in the composition of the terpolymers.…”
Section: Modular N-nј Ligands For the Copolymerisation Of Co And Styrenementioning
confidence: 99%
“…[51] This effect is shown in Figure 10 The cationic palladium systems [PdMe(NCMe)(N-NЈ)]-[BArF] containing imidazolyl-pyridine ligands cis-12, cis-13, cis-and trans-15 and pyrazolyl-pyridines 18, 20 and 21 have also been used for the terpolymerisation of CO/TBS/ ethene. [50,52] It was found that the choice of the olefin preferentially inserted into the terpolymer is strictly related to the nature of the nitrogen ligand present in the catalyst and not only to the kind of ligand. Thus, a slight modification in the chelating N ligands coordinated to palladium terpolymerisation catalysts leads to unexpected results in the composition of the terpolymers.…”
Section: Modular N-nј Ligands For the Copolymerisation Of Co And Styrenementioning
confidence: 99%
“…More recently, the use of the cationic palladium systems [PdMe(NCMe)(N -N ′ )] [BArF] containing pyridine -imidazoline ligands cis -107a , cis -107b , and cis and trans -107d was reported in the terpolymerization of CO/TBS/ethane, and circular dichroism analysis of the terpolymer obtained with the enantiomerically pure ligand 107d shows that it is optically active [119] .…”
Section: Asymmetric Co /Olefi Ns Terpolymerizationmentioning
confidence: 99%
“…We have previously shown that in the CO/tert-butylstyrene/ethylene terpolymerization catalyzed by ½PdðMeÞðNCMeÞðN -N 0 Þ½BAr 0 4 complexes [Ar 0 = 3,5-(CF 3 ) 2 C 6 H 3 ], where N-N 0 = pyridine-imidazoline and pyrazolyl-pyrimidine ligands, the olefin preferentially inserted in the terpolymer chain is strictly related to the nature of the nitrogen ligand [27].…”
Section: Introductionmentioning
confidence: 99%